The association of handgrip strength with all-cause and cardiovascular mortality: results from the National Health and Nutrition Examination Survey database prospective cohort study with propensity score matching - Xiong, Lijiao; Zeng, Zhaohao; Wang, Shuojia; Liao, Tingfeng; Wang, Xiaohao; Wang, Xinyu; Yang, Guangyan; Li, Yanchun; Li, Lixing; Zhu, Jing; Zhao, Pengfei; Yang, Shu; et al. (Frontiers in Nutrition, 2023)
Objection: To investigate the association between handgrip strength (HGS) with all-cause and cardiovascular disease (CVD) mortality in US adults. Method: We analyzed data from the National Health and Nutrition Examination Survey (NHANES) prospective cohort study (2011-2014) with 10,470 participants. The cox regression analysis, Kaplan-Meier survival curves, fitted curves, ROC curves, and propensity score-matched analysis (PSM) with inverse probability of treatment weighting (IPTW), SMRW (PSM with Repeated Weights), PA (pairwise algorithm), and OW (Overlap Weighting) regression analysis were performed to assess the relationship between HGS and all-cause and CVD mortality. Results: The low HGSs (men<37.4 Kg, women<24 Kg), was found to be associated with higher all-cause and CVD mortality in a reverse J-shaped curve (P<0.05). Adjusting for multiple covariates including age, BMI, race, education level, marriage status, smoking and alcohol use, and various comorbidities, the hazard ratio (HR) for all-cause mortality in the lowest HGS quintile 1(Q1) was 3.45 (2.14-5.58) for men and 3.3 (1.88-5.79) for women. For CVD mortality, the HR was 2.99 (1.07-8.37) for men and 10.35 (2.29-46.78) for women. The area under the curve (AUC) for HGS alone as a predictor of all-cause mortality was 0.791 (0.768-0.814) for men and 0.780 (0.752-0.807) for women (P<0.05), while the AUC for HGS and age was 0.851 (0.830-0.871) for men and 0.848 (0.826-0.869) for women (P<0.05). For CVD mortality, the AUC for HGS alone was 0.785 (95% CI 0.738-0.833) for men and 0.821 (95% CI 0.777-0.865) for women (P<0.05), while the AUC for HGS and age as predictors of all-cause mortality was 0.853 (0.861-0.891) for men and 0.859 (0.821-0.896) for women (P<0.05). The HGS Q1 (men <37.4 kg and women <24 kg) was matched separately for PSM. After PSM, IPTW, SMRW, PA, and OW analyses, women had 2.37-3.12 and 2.92-5.12 HRs with low HGS for all-cause and CVD mortality, while men had 2.21-2.82 and 2.33-2.85 for all-cause and CVD mortality, respectively. (p < 0.05). Conclusion: Adults with low HGS exhibited a significantly increased risk of both all-cause and CVD mortality, regardless of gender. Additionally, low HGS served as an independent risk factor and predictor for both all-cause and CVD mortality.